Pengaruh Bahan Pengisi Cangkang Kelapa Sawit Komposit-Silicone Rubber Dalam Permulaan Pemohonan Listrik - Fitriah, Fitriah; Kurnianto, Rudi; Rajagukguk, Managam (ELKHA : Jurnal Teknik Elektro, 2020)
Inception of electrical treeingÂ  can irreversibly deteriorate the insulation of polymeric power cables leading to a complete failure and initial process of degradation in polymer insulation due to a void that experiences high electric field stress in the material. This paper present will study fillerâ€™s influence on inception of electrical treeing growth in silicone rubber â€“ oil palm endokaprium composite.Â  The observed data is inception voltage and time phenomena in two types of test sample, that is " with filler " and " without filler ". Sample of filler consisted of silicone rubber and oil palm endokaprium composite for oil palm endokaprium weight is 0.1 grams and weight silicone rubber 3.9 gram. While the sample without filler is only silicone rubber . It is obtained that the tree inception voltages dan time for â€œwithâ€ dan â€œwithout fillerâ€ specimens are 8 kV / 182 seconds and 7,5 kV / 137 seconds, respectivelly.. It is considered that â€œfillerâ€Â  acted as a barrier for tree inception. We throught that â€œfillerâ€ enhanced dielectric strength of silicone rubber and oil palm endokaprium by disturbing high electric field stress, result in higher tree inception voltage and longer tree inception time.